Scouring-resistant atomizing disc coating and preparation method thereof

By designing a multi-layer coating structure on the atomized disk, using materials such as high molybdenum nickel-based self-melting alloy powder, nickel-based self-melting alloy, etc. to form a high-hardness protective film, and applying self-cleaning coatings on the surface, the problems of insufficient corrosion resistance, wear resistance and self-cleaning capacity of the atomized disk in the prior art are solved, and a longer service life and lower maintenance costs are achieved.

CN119530698APending Publication Date: 2025-02-28GUANGDONG YUEKE NEW MATERIALS TECH CO LTD

Patent Information

Application Number
CN202411713402.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The prior art is difficult to simultaneously improve the corrosion resistance, wear resistance and self-cleaning ability of the atomized disc, resulting in insufficient service life in corrosive and wearable environments.

Method used

A multi-layer coating structure is adopted, including a base layer, a high-molybdenum nickel-based self-melt alloy powder as the basis and an intermediate layer. A high-hardness and high wear resistance protective film are formed through materials such as nickel-based self-melt alloy, WC, Ti3Al alloy, and surface layer. A self-cleaning coating with components such as TiO2, polytetrafluoroethylene dispersion emulsion, silicon sol and α-methylphenylmethylhydrogen-containing polysiloxane are used.

Benefits of technology

The high corrosion resistance, wear resistance and self-cleaning capability of the atomized disk is achieved, extending its service life and reducing maintenance costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119530698A_ABST
    Figure CN119530698A_ABST
Patent Text Reader

Abstract

The invention provides a washing-resistant atomizing disc coating and a preparation method thereof, and belongs to the field of coatings. The coating comprises a bottom layer, the bottom layer is attached to the surface of the atomizing disc, and spraying paint of the bottom layer is high-molybdenum nickel-based self-fluxing alloy powder; the middle layer is attached to the surface of the bottom layer, and a spraying material of the middle layer is prepared from, by weight, 20-50 parts of nickel-based self-fluxing alloy powder, 10-25 parts of WC, 5-10 parts of Ti3Al alloy, 5-15 parts of alpha-ZrP, 2-10 parts of molybdate, 2-5 parts of silicate, 5-10 parts of SiO2 and 4-8 parts of Al2O3; the surface layer is attached to the surface of the middle layer, and coating of the surface layer is self-cleaning coating. Therefore, the corrosion resistance, the wear resistance and the self-cleaning capability of the atomizing disc are improved at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of coatings, and in particular to a coating of an atomizing disk resistant to erosion and a preparation method thereof. Background Art

[0002] Atomizer disk is a device installed on atomizer or related equipment to atomize liquid into tiny particles. Its working principle is usually to generate centrifugal force or shear force on the surface of the atomizer disk through high-speed rotation or specific fluid dynamics design, thereby dispersing the liquid into fine droplets. Atomizer disk usually consists of a disc-shaped body, nozzle, sleeve and other parts. The disc-shaped body is the core part of the atomizer disk, and its surface is designed with a specific texture or structure to optimize the atomization effect.

[0003] During operation, the atomizer disc may come into contact with various corrosive liquids or gases, such as acidic or alkaline solutions. A highly corrosion-resistant surface can effectively resist the erosion of these corrosive substances and extend the service life of the atomizer disc. The atomizer disc is subjected to greater friction and impact forces during high-speed rotation or spraying. A highly wear-resistant surface can reduce the wear of these forces on the atomizer disc and extend its service life. During use, the atomizer disc may accumulate various dirt, such as dust, grease, etc. These dirt will affect the atomization effect and performance of the atomizer disc. The self-cleaning ability can prevent dirt from accumulating on the surface of the atomizer disc and keep its surface clean and smooth. In the prior art, a PVD coating is provided on the surface of the atomizer disc, and the coating is thinner than 10μm. However, the rotation speed of the atomizer disc is as high as 8000 to 12000 rpm, and the corrosion resistance and erosion resistance of the atomizer disc provided with a PVD coating cannot meet the service life requirements of 6 to 12 months. Chinese patent CN114016028B discloses a thin-wall titanium alloy substrate high temperature resistant and anti-scouring composite coating and its preparation method, but the composite coating has no self-cleaning performance, and dirt is easy to accumulate on the surface of the atomizing disk. Therefore, how to simultaneously improve the corrosion resistance, wear resistance and self-cleaning ability of the atomizing disk is a technical problem that needs to be solved urgently. Summary of the invention

[0004] The present application provides a scour-resistant coating of an atomizing disk and a preparation method thereof to solve the following technical problem: how to simultaneously improve the corrosion resistance, wear resistance and self-cleaning ability of the atomizing disk.

[0005] In a first aspect, the present application provides a coating of an atomizing disk that is resistant to erosion, the coating comprising:

[0006] A bottom layer, the bottom layer is attached to the surface of the atomizing disk, and the spray coating of the bottom layer is a high-molybdenum-nickel-based self-fluxing alloy powder;

[0007] an intermediate layer, the intermediate layer being attached to the surface of the bottom layer, wherein the spray coating material of the intermediate layer comprises, by weight: 20 to 50 parts of nickel-based self-fluxing alloy powder, 10 to 25 parts of WC, 5 to 10 parts of Ti3Al alloy, 5 to 15 parts of α-ZrP, 2 to 10 parts of molybdate, 2 to 5 parts of silicate, 5 to 10 parts of SiO2 and 4 to 8 parts of Al2O3, 1 to 3 parts of cerium oxide, and 1 to 3 parts of lanthanum oxide; and

[0008] The surface layer is attached to the surface of the middle layer. The coating of the surface layer is a self-cleaning coating. The components of the self-cleaning coating include: TiO2, polytetrafluoroethylene dispersion emulsion, silica sol, α-methylphenethylmethyl hydrogen-containing polysiloxane.

[0009] Optionally, the nickel-based self-fluxing alloy powder includes one or more of NiCo23Cr17Al12Y0.5, NiCo23Cr20Al8.5Ta4Y0.1 and CoNi32Cr21Al8Y0.5, and the average particle size of the nickel-based self-fluxing alloy powder is 20 to 30 μm.

[0010] Optionally, the silicate includes one or more of mica powder, calcium silicate, aluminum silicate and alkali metal silicate, and the molybdate includes one or more of alkali metal molybdate, magnesium molybdate and thallium molybdate.

[0011] Optionally, the silicate is mica powder and aluminum silicate, and the mass ratio of the mica powder to the aluminum silicate is (1-3):1.

[0012] Optionally, the self-cleaning coating comprises, in parts by weight: 20 to 50 parts of TiO2, 10 to 30 parts of polytetrafluoroethylene dispersion emulsion, 20 to 40 parts of silica sol, and 10 to 20 parts of α-methylphenethylmethyl hydrogen-containing polysiloxane.

[0013] Optionally, the thickness of the bottom layer is 50-100 μm, the thickness of the middle layer is 200-500 μm, and the thickness of the surface layer is 40-80 μm.

[0014] Optionally, the coating meets the following properties: microhardness HV ≥ 500, porosity < 0.5%, and the service life of the atomizer disk having the coating on the surface is > 12 months.

[0015] In a second aspect, the present application provides a method for preparing a coating as described in any one embodiment of the first aspect, the method comprising:

[0016] The atomizing disk is shot peened;

[0017] Spraying a bottom layer of spray paint onto the surface of the atomizing disk to form a bottom layer on the surface of the atomizing disk;

[0018] Spraying the spray coating material of the intermediate layer onto the surface of the bottom layer to form an intermediate layer on the surface of the bottom layer;

[0019] The atomizing disk having the bottom layer and the middle layer is subjected to induction remelting, and then cooled to room temperature;

[0020] The coating material of the surface layer is applied to the surface of the intermediate layer and then dried to form the surface layer on the surface of the intermediate layer.

[0021] Optionally, the spraying adopts an atmospheric plasma spraying process, and the parameters of the atmospheric plasma spraying process include: argon flow rate of 25-35L / min, hydrogen flow rate of 5-10L / min, current control of 500-550A, power of 25-35kW, powder feeding argon flow rate of 1.0-3.0L / min, powder feeding speed of 50-70g / min, and spraying distance of 80-100mm.

[0022] Optionally, the parameters of the induction remelting include: a melting temperature of 1300 to 1400° C. and a melting time of 60 to 180 s.

[0023] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:

[0024] The present application provides a coating for an atomizer disk that is resistant to erosion. First, the thermal expansion coefficients of the bottom layer, the middle layer and the surface layer are designed to decrease in sequence, so that the coating can better disperse and balance the thermal stress when the temperature changes, thereby improving the overall stability and adhesion of the coating; secondly, the chemical components of the middle layer are reasonably designed, and the components are intertwined and tightly combined during the spraying process to form a protective film with excellent corrosion resistance and wear resistance, thereby improving the corrosion resistance and wear resistance of the atomizer disk; thirdly, the chemical components of the surface layer are reasonably designed, and the components act on the surface of the coating in various ways such as photocatalysis, hydrophobic effect, filling and thickening, adjustment of surface properties and chemical bonding, thereby having excellent self-cleaning performance; finally, the three act together to simultaneously improve the corrosion resistance, wear resistance and self-cleaning ability of the atomizer disk. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.

[0026] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0027] Figure 1 A schematic structural diagram of a coating of an atomizing disk that is resistant to erosion provided in an embodiment of the present application;

[0028] Figure 2 A flow chart of a method for preparing a coating of an atomizing disk that is resistant to erosion provided in an embodiment of the present application;

[0029] Reference numerals:

[0030] 1-atomizing disk substrate, 2-coating layer, 21-bottom layer, 22-middle layer, 23-surface layer. DETAILED DESCRIPTION

[0031] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0032] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.

[0033] Figure 1 A schematic structural diagram of a coating of an atomizing disk that is resistant to erosion provided in an embodiment of the present application.

[0034] The present application provides a coating for an atomizing disk that is resistant to erosion, such as Figure 1 As shown, the coating comprises:

[0035] A bottom layer, the bottom layer is attached to the surface of the atomizing disk, and the spray coating of the bottom layer is a high-molybdenum-nickel-based self-fluxing alloy powder;

[0036] an intermediate layer, the intermediate layer being attached to the surface of the bottom layer, wherein the spray coating material of the intermediate layer comprises, by weight: 20 to 50 parts of nickel-based self-fluxing alloy powder, 10 to 25 parts of WC, 5 to 10 parts of Ti3Al alloy, 5 to 15 parts of α-ZrP, 2 to 10 parts of molybdate, 2 to 5 parts of silicate, 5 to 10 parts of SiO2 and 4 to 8 parts of Al2O3, 1 to 3 parts of cerium oxide, and 1 to 3 parts of lanthanum oxide; and

[0037] The surface layer is attached to the surface of the middle layer. The coating of the surface layer is a self-cleaning coating. The self-cleaning coating includes: TiO2, polytetrafluoroethylene dispersion emulsion, silica sol, α-methylphenethylmethyl hydrogen-containing polysiloxane.

[0038] In some embodiments, the self-cleaning coating comprises, by weight: 20 to 50 parts of TiO2, 10 to 30 parts of polytetrafluoroethylene dispersion emulsion, 20 to 40 parts of silica sol, and 10 to 20 parts of α-methylphenethylmethyl hydrogen-containing polysiloxane.

[0039] First, high molybdenum nickel-based alloy powder has the following effects: (1) High corrosion resistance: The high molybdenum content makes the nickel-based alloy have excellent corrosion resistance and can resist the erosion of various corrosive media. (2) High wear resistance: The nickel-based alloy itself has good mechanical properties, and the hardening effect of molybdenum makes the alloy have higher hardness and wear resistance. (3) Good wettability and adhesion: The high molybdenum nickel-based alloy powder can wet the stainless steel substrate well during the spraying process to form a close bond.

[0040] Molybdenum plays a vital role in this alloy powder, as follows: (1) Enhanced solid solution strength: Most molybdenum atoms dissolve in the solid solution of the nickel matrix, increasing the lattice constant of the solid solution and thus enhancing the strength of the solid solution. This enhanced strength helps to form a stronger bond between the coating and the substrate. (2) Improved thermal stability: The addition of molybdenum can also improve the thermal stability of the alloy, allowing the coating to maintain its structure and performance stability in a high temperature environment. This helps the coating resist high temperature erosion and corrosion during the operation of the atomizer disk, thereby extending its service life. (3) Optimized microstructure: The addition of molybdenum helps to refine the microstructure of the coating and reduce defects such as pores and cracks. This optimized microstructure improves the density and uniformity of the coating, thereby enhancing the bonding between the coating and the substrate. (4) Promoted interactions between elements: In high-molybdenum nickel-based self-fluxing alloy powders, molybdenum and other alloying elements (such as chromium, iron, cobalt, etc.) interact with each other. These interactions help to form a more complex alloy structure, thereby improving the overall performance and bonding ability of the coating.

[0041] At the same time, the bottom layer can improve the bonding strength between the middle layer and the stainless steel substrate of the atomizer disk. The improvement of the bonding strength is mainly due to the combined effect of multiple mechanisms such as metallurgical bonding, physical adsorption and chemical bonding, element diffusion and alloying, and the transition effect of the bottom layer. The specific reasons are as follows: (1) Metallurgical bonding: During the spraying process, the high-molybdenum nickel-based alloy powder melts and cools rapidly, forming a metallurgical bond with the stainless steel substrate. This bonding mode is formed by mutual diffusion and reaction between atoms and has a very high bonding strength. (2) Physical adsorption and chemical bonding: There are some active functional groups or defects on the surface of the high-molybdenum nickel-based alloy powder. These functional groups or defects can be physically adsorbed and chemically bonded with atoms or molecules on the surface of the stainless steel substrate, further enhancing the bonding strength. (3) Element diffusion and alloying: During the spraying, induction remelting and cooling process, the elements (such as nickel, molybdenum, etc.) in the high-molybdenum nickel-based alloy powder will diffuse into the stainless steel substrate to form a diffusion layer. This diffusion layer can increase the bonding area and bonding strength between the coating and the substrate. (4) Transition effect of the bottom layer: The middle layer contains a variety of high-performance materials, such as WC, Ti3Al alloy, etc. These materials have good compatibility and wettability with the high-molybdenum nickel-based alloy powder and can form a close bond. Therefore, the bottom layer can further increase the bonding strength between the coating and the substrate, playing a transition and buffering role.

[0042] Second, the present application rationally designs the chemical components of the intermediate layer, and the functions of each component are as follows:

[0043] Nickel-based self-fluxing alloy powder: Nickel-based self-fluxing alloy powder is the main component of the coating, which provides basic mechanical properties and corrosion resistance. Nickel element has good toughness and ductility, and can form a continuous metal network in the coating, enhancing the overall strength of the coating.

[0044] WC: WC is a hard phase in the coating, with extremely high hardness and wear resistance. It can resist wear and cutting, protecting the substrate from damage. In the coating, WC particles are combined with nickel-based alloy powder through metal bonds to form a strong wear-resistant layer.

[0045] Ti3Al alloy: Ti3Al alloy has good oxidation resistance and high temperature stability. It can form a dense oxide film under high temperature environment to protect the coating from oxidation corrosion. Under high temperature, aluminum atoms easily combine with oxygen atoms to form an aluminum oxide film, which can prevent oxygen atoms from further diffusing into the coating, thereby protecting the coating from oxidation corrosion.

[0046] α-ZrP (phosphite zircon): The zirconium atoms and phosphate ions in the α-ZrP molecule are bonded by ionic bonds to form a layered structure. This structure gives α-ZrP excellent lubrication properties. In the coating, α-ZrP particles can fill between metal particles to form a tiny lubrication layer, reducing friction and wear, thereby reducing the friction coefficient between the coating and the friction medium and reducing the wear rate.

[0047] Molybdate: Molybdate has excellent corrosion inhibition performance and can form a protective film on the metal surface to effectively block the erosion of corrosive media (such as moisture, oxygen, chloride ions, etc.). The formation of this protective film is due to the chemical reaction between molybdate and the metal surface, which can form a dense oxide film or composite film on the metal surface. This film can significantly improve the corrosion resistance of the metal. Especially in some harsh environments, such as high temperature, high humidity, high salinity, etc., the corrosion inhibition effect of molybdate is more obvious. At the same time, molybdate can inhibit the release of metal ions in the coating, thereby slowing down the corrosion process.

[0048] Silicate: Silicate can enhance the weather resistance and water resistance of the coating and improve the durability of the coating. It can also form a silicate glass phase with other elements in the coating, fill the pores in the coating and improve the density of the coating. In the coating, silicate can form a silicate glass phase with other elements (such as aluminum, silicon, etc.), which has excellent weather resistance and water resistance. At the same time, the silicate glass phase can also fill the pores in the coating, improving the density and corrosion resistance of the coating.

[0049] SiO2: SiO2 can enhance the hardness and wear resistance of the coating. It can also form a silicate glass phase or a silicon-oxygen network structure with other elements in the coating to improve the overall performance of the coating. In the coating, SiO2 particles can form a silicate glass phase or a silicon-oxygen network structure with other elements (such as aluminum, silicon, etc.), which can enhance the hardness and wear resistance of the coating.

[0050] Al2O3: Al2O3 has excellent hardness and wear resistance. It can also form stable compounds or solid solutions with other elements in the coating to improve the overall performance of the coating. In the coating, Al2O3 particles can form stable compounds or solid solutions with other elements (such as nickel, silicon, etc.), which have excellent hardness and wear resistance.

[0051] Cerium oxide (CeO2): Cerium oxide is an inorganic substance with stable chemical properties and is not easy to react with other substances. This stability helps the coating maintain its performance in harsh environments and reduces coating damage caused by chemical reactions. Cerium oxide can exist in the coating in the form of particles. When added in a moderate amount, it can make the coating surface denser, reduce pores and defects in the coating, and thus improve the erosion resistance of the coating. In addition, cerium oxide can act as a barrier layer to prevent corrosive substances or erosion media from directly contacting and eroding the substrate under the coating, thereby extending the service life of the coating.

[0052] Lanthanum oxide (La2O3) Lanthanum oxide has strong oxidizing properties, which enables it to be used as a passivator in the coating to passivate the metal particles in the coating and reduce their reactivity with the external environment, thereby improving the corrosion resistance of the coating. At the same time, lanthanum oxide can also exist in the coating in the form of particles, and improve the density and erosion resistance of the coating by improving the microstructure of the coating, such as refining the grains and reducing the pores. Similar to cerium oxide, lanthanum oxide also has good chemical stability and can maintain its performance unchanged in a variety of environments, thereby protecting the coating from damage. The addition of lanthanum oxide can also enhance the adhesion between the coating and the substrate, making the coating more firmly attached to the surface of the substrate and improving the overall erosion resistance of the coating.

[0053] At the same time, during the spraying process, the chemical components of the intermediate layer are intertwined through metallurgical bonding, chemical reaction and physical action to form a dense protective film with excellent corrosion resistance. This protective film can block the corrosion of the corrosive medium on the substrate and improve the hardness and wear resistance of the coating. The details are as follows: (1) Metallurgical bonding: During the spraying process, the high temperature causes the nickel-based self-fluxing alloy powder, WC, Ti3Al alloy and other components to melt and penetrate each other. These components are tightly bonded through chemical bonding such as metal bonds or covalent bonds to form a tight coating structure. This metallurgical bonding not only enhances the overall strength of the coating, but also forms a good bonding force between the coating and the substrate, thereby improving the corrosion resistance of the coating. (2) Chemical reaction: During the spraying and subsequent cooling process, chemical reactions may occur between the molybdate, silicate, SiO2 and Al2O3 components and between them and components such as nickel-based alloys. These reactions may include oxidation, reduction, substitution, complexation, etc., to form complex compounds or solid solutions. These compounds or solid solutions usually have higher chemical stability and corrosion resistance, and can more effectively prevent the erosion of the coating by the corrosive medium. (3) Physical effect: Components such as α-ZrP (phosphite zircon) play a physical role in the coating, such as lubrication and friction reduction. These components usually have a layered structure or special surface properties, which can form a lubricating film between the coating and the friction medium to reduce friction and wear. In addition, components such as α-ZrP can also fill the tiny pores in the coating, improving the density and corrosion resistance of the coating. (4) Optimizing the coating structure: Cerium oxide and lanthanum oxide can refine the grains in the coating, reduce defects such as pores and cracks, and improve the density and uniformity of the coating. The addition of hard particles such as WC and Ti3Al alloy can optimize the structure of the coating, form a more solid protective layer, and improve the wear resistance and erosion resistance of the coating. In a corrosive environment, cerium oxide and lanthanum oxide can form a dense protective film to prevent corrosive substances from corroding the substrate. Their synergistic effect can make this protective film more solid and durable, thereby improving the corrosion resistance of the coating. (5) Synergistic effect: The interaction and synergistic effect between these components together form a protective film with excellent corrosion resistance. This protective film not only has high chemical stability and corrosion resistance, but also has high hardness and wear resistance. It can effectively block the erosion of the corrosive medium on the substrate, while reducing the friction and wear between the coating and the friction medium, thereby improving the corrosion resistance and wear resistance of the atomizing disk.

[0054] In summary, through the carefully designed spraying materials, the various components can be intertwined and closely combined during the spraying process to form a protective film with excellent corrosion resistance and wear resistance. This protective film can not only improve the corrosion resistance and wear resistance of the atomizing disc, but also extend its service life and reduce maintenance costs.

[0055] Third, the present application rationally designs the chemical components of the surface layer, and each component plays its own unique role from a molecular perspective, together forming an efficient and durable self-cleaning system. The specific functions of each component are as follows:

[0056] TiO2: TiO2 plays a major role in photocatalysis in self-cleaning coatings. Under ultraviolet light, TiO2 molecules can absorb light energy and generate electron-hole pairs. These electrons and holes are highly active and can trigger a series of chemical reactions. The electrons react with oxygen molecules adsorbed on the surface of TiO2 to generate superoxide anion radicals (O 2- ), while the holes react with the adsorbed water molecules or hydroxide ions to generate hydroxyl radicals (·OH). These free radicals have strong oxidizing ability and can decompose organic matter, dirt and bacteria attached to the surface of the coating, thereby achieving a self-cleaning effect. In addition, TiO2 also has excellent UV shielding ability, which can protect the coating from UV damage and extend its service life.

[0057] Polytetrafluoroethylene dispersion (PTFE): PTFE mainly provides excellent lubricity and hydrophobicity in self-cleaning coatings. PTFE molecules have extremely low surface energy, which makes the coating surface extremely hydrophobic. Water droplets cannot form a continuous water film on the surface of the PTFE coating, but appear as tiny water droplets, which can easily slide down and take away the dirt on the surface. The interaction between PTFE molecular chains is weak, which makes the coating surface have a low friction coefficient. This lubricity can reduce the friction and adhesion between the coating and the dirt, making it easier to wash away the dirt. In addition, PTFE also has excellent chemical resistance and temperature resistance, which can protect the coating from the erosion of chemicals and the influence of high temperature.

[0058] Silica sol: Silica sol plays a major role in filling, thickening and reinforcing in self-cleaning coatings. The silicon dioxide (SiO2) nanoparticles in silica sol can fill tiny pores and defects in the coating, improving the density and smoothness of the coating. Silica sol has high viscosity, which can increase the viscosity and thixotropy of the coating, making it easier for the coating to form a uniform coating during construction. SiO2 nanoparticles can form chemical bonds or physical adsorption with other components in the coating (such as resins, etc.), thereby enhancing the overall strength and durability of the coating. In addition, silica sol can also improve the weather resistance and chemical resistance of the coating, enabling it to maintain stable performance in harsh environments.

[0059] α-Methylphenethylmethyl hydrogen-containing polysiloxane: α-Methylphenethylmethyl hydrogen-containing polysiloxane mainly plays the role of adjusting the surface performance of the coating and enhancing the adhesion in self-cleaning coatings. The silicon-oxygen bond (Si-O) in the compound molecule has excellent flexibility and stability, which can make the coating surface smoother and more delicate. The methyl and phenethyl groups can improve the compatibility and adhesion between the coating and the substrate and enhance the adhesion of the coating. The hydrogen-containing group (Si-H) can react chemically with other components in the coating under certain conditions (such as addition reaction, etc.) to form a stronger chemical bond, further improving the overall performance and durability of the coating. In addition, the compound can also give the coating a certain degree of hydrophobicity and lubricity, which helps to reduce the adhesion of dirt and wash away the dirt that has already attached.

[0060] In the self-cleaning coating on the surface, the synergistic effect of each component is mainly reflected in the following aspects: (1) Synergy of photocatalysis and hydrophobicity: The photocatalytic effect of TiO2 can decompose organic matter and dirt on the surface of the coating, while the hydrophobic effect of PTFE can accelerate the detachment and flushing process of dirt. The synergistic effect of the two improves the self-cleaning efficiency of the coating. (2) Synergy of silica sol and PTFE: The filling effect of silica sol improves the density and flatness of the coating, which is beneficial to the arrangement and distribution of PTFE molecular chains, thereby further enhancing the lubricity and hydrophobicity of the coating. (3) Synergy of α-methylphenethylmethyl hydrogen-containing polysiloxane with other components: This compound improves the adhesion, durability and self-cleaning performance of the coating together with other components by adjusting the surface properties of the coating and enhancing chemical bonding.

[0061] In summary, the interactions and reactions of the various components in the surface self-cleaning coating from a molecular perspective are complex and subtle. They work together on the coating surface through photocatalysis, hydrophobicity, filling and thickening, adjusting surface properties and chemical bonding, forming a coating system with excellent self-cleaning performance, weather resistance, chemical resistance and adhesion.

[0062] 4. The coating of the present application is composed of a bottom layer, an intermediate layer and a surface layer, and has the following advantages:

[0063] Bottom layer design. (1) Material selection: High molybdenum nickel-based self-fluxing alloy powder as the bottom layer material has good wear resistance, corrosion resistance and high temperature performance, and is very suitable as the bottom layer of the atomizer disk. (2) Thermal expansion coefficient: The thermal expansion coefficient of the high molybdenum nickel-based alloy is moderate and is relatively close to the thermal expansion coefficient of the atomizer disk substrate, which helps to reduce the thermal stress caused by the difference in thermal expansion.

[0064] Intermediate layer design. (1) Composition optimization: The intermediate layer is made of a composite spray of multiple materials, including nickel-based self-fluxing alloy powder, WC, Ti3Al alloy, α-ZrP, molybdate, silicate, SiO2 and Al2O3. The combination of these materials gives the intermediate layer high strength, good toughness and wear resistance. (2) Thermal expansion coefficient matching: The thermal expansion coefficient of the intermediate layer is designed to be lower than that of the underlying layer, which helps to further disperse and balance thermal stress when the temperature changes and reduce the risk of cracking of the coating. (3) Density improvement: The multi-layer structure and the combination of multiple materials increase the number of interfaces inside the intermediate layer, and the atomic arrangement at the interface is more compact, which helps to improve the density of the coating.

[0065] Surface design. (1) Self-cleaning function: The surface layer adopts self-cleaning coating, including TiO2, polytetrafluoroethylene dispersion emulsion, silica sol and α-methylphenethylmethyl hydrogen-containing polysiloxane. The combination of these ingredients makes the surface layer have excellent self-cleaning performance and can resist the adhesion and erosion of pollutants. (2) Further reduction of thermal expansion coefficient: The thermal expansion coefficient of the surface layer is designed to be lower than that of the middle layer, which helps to further reduce thermal stress when the temperature changes and improve the overall stability of the coating. (3) Wear resistance and erosion resistance: Self-cleaning coatings generally also have good wear resistance and erosion resistance, which can protect the atomizing disk from erosion and wear.

[0066] Overall analysis. (1) Matching of thermal expansion coefficients: By designing the thermal expansion coefficients of the bottom layer, middle layer and surface layer to decrease in sequence, the coating can better disperse and balance thermal stress when the temperature changes, thereby improving the overall stability and adhesion of the coating. (2) Advantages of multilayer structure: The multilayer structure not only improves the density and strength of the coating, but also increases the functionality of the coating (such as self-cleaning performance). At the same time, the interface effect in the multilayer structure also helps to prevent the expansion of cracks and improve the durability of the coating.

[0067] In summary, the design of the erosion-resistant atomizer disc coating fully considers the performance matching of materials, the control of thermal expansion coefficient, and the improvement of coating density by multi-layer structure. This design is expected to show excellent wear resistance, erosion resistance and self-cleaning performance in practical applications.

[0068] In some embodiments, the nickel-based self-fluxing alloy powder includes one or more of NiCo23Cr17Al12Y0.5, NiCo23Cr20Al8.5Ta4Y0.1 and CoNi32Cr21Al8Y0.5, and the average particle size of the nickel-based self-fluxing alloy powder is 20 to 30 μm.

[0069] In some embodiments, the silicate includes one or more of mica powder, calcium silicate, aluminum silicate and alkali metal silicate, and the molybdate includes one or more of alkali metal molybdate, magnesium molybdate and thallium molybdate.

[0070] In some embodiments, the silicate is mica powder and aluminum silicate, and the mass ratio of the mica powder to the aluminum silicate is (1-3):1.

[0071] Mica powder is a layered silicate mineral, consisting of two layers of silicon-oxygen tetrahedrons sandwiched by a layer of aluminum-oxygen octahedrons. It has excellent insulation, high temperature resistance and corrosion resistance. The silicon atoms and aluminum atoms in the aluminum silicate molecules are connected by oxygen atoms to form a network structure. This structure gives aluminum silicate high strength and hardness, as well as good heat resistance and corrosion resistance. When mica powder is mixed with aluminum silicate, their molecular structures are intertwined in space, forming a more complex and stable structure. This structure not only improves the overall strength of the coating, but also enhances its heat resistance and corrosion resistance.

[0072] In some embodiments, the thickness of the bottom layer is 50-100 μm, the thickness of the middle layer is 200-500 μm, and the thickness of the surface layer is 40-80 μm.

[0073] In some embodiments, the coating meets the following properties: microhardness HV ≥ 500, porosity < 0.5%, and the service life of the atomizer disk having the coating on its surface is > 12 months.

[0074] Figure 2 A flow chart of a method for preparing a coating of an atomizing disk that is resistant to erosion provided in an embodiment of the present application.

[0075] Based on a general inventive concept, the present application provides a method for preparing a coating as described in any one of the above embodiments, such as Figure 2 As shown, the method includes:

[0076] S1. Shot peening the atomizing disk;

[0077] Through shot peening, the roughness of the atomizing disk surface is increased, and the adhesion of the subsequent spray layer is improved.

[0078] S2, spraying the bottom layer of spray coating onto the surface of the atomizing disk to form a bottom layer on the surface of the atomizing disk;

[0079] In some embodiments, the spraying adopts an atmospheric plasma spraying process, and the parameters of the atmospheric plasma spraying process include: an argon flow rate of 25 to 35 L / min, a hydrogen flow rate of 5 to 10 L / min, a current control of 500 to 550 A, a power of 25 to 35 kW, a powder feeding argon flow rate of 1.0 to 3.0 L / min, a powder feeding speed of 50 to 70 g / min, and a spraying distance of 80 to 100 mm.

[0080] Argon flow rate: 25-35L / min, used to protect the spraying area and prevent oxidation. Hydrogen flow rate: 5-10L / min, as a component of plasma gas, participates in the formation of plasma. Current size: 500-550A, controls the temperature and energy of plasma. Power: 25-35kW, provides the energy required for spraying. Powder feeding argon flow rate: 1.0-3.0L / min, used to feed the spray material into the plasma beam. Powder feeding speed: 50-70g / min, controls the supply amount of spray material. Spraying distance: 80-100mm, ensures uniform spraying and no overheating.

[0081] S3, spraying the spray coating material of the middle layer onto the surface of the bottom layer to form the middle layer on the surface of the bottom layer;

[0082] S4, induction remelting the atomizing disk having the bottom layer and the middle layer, and then cooling to room temperature;

[0083] The atomized disk with the bottom layer and the middle layer is placed in an induction heating device for induction remelting. The melting temperature and melting time are controlled to ensure that the coating is completely melted and rearranged. Subsequently, the coating is allowed to cool naturally to room temperature. Through induction remelting, the powder particles in the bottom layer and the middle layer are melted and rearranged to form a dense and uniform structure, which improves the overall performance of the coating.

[0084] In some embodiments, the parameters of the induction remelting include: a melting temperature of 1300 to 1400° C., and a melting time of 60 to 180 s.

[0085] The melting temperature is set at 1300-1400℃, and the melting time is set at 60-180s, which can ensure that the coating materials (such as mica powder, aluminum silicate, etc.) are completely melted. Melting is a key step for the coating materials to rearrange and form a dense structure, which has a decisive influence on the final performance of the coating. At the same time, at high temperatures, the elements in the coating material can diffuse, which helps to form a uniform alloying structure. This is of great significance for improving the mechanical properties, corrosion resistance and heat resistance of the coating. In addition, the appropriate melting temperature can cause the coating to form a fine and uniform organizational structure, reduce pores and defects, and thus improve the overall performance of the coating.

[0086] S5, applying a surface coating to the surface of the intermediate layer, and then drying to form a surface layer on the surface of the intermediate layer.

[0087] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are usually measured according to industry standards. If there is no corresponding industry standard, then the conditions recommended by the manufacturer are followed.

[0088] Example 1

[0089] This embodiment provides a coating of an atomizing disk that is resistant to erosion, and the coating comprises:

[0090] A bottom layer, the bottom layer is attached to the surface of the atomizing disk, and the spray coating of the bottom layer is a high-molybdenum nickel-based self-fluxing alloy powder (model N06950 nickel alloy);

[0091] An intermediate layer, the intermediate layer is attached to the surface of the bottom layer, and the spray coating of the intermediate layer is, by weight: 35 parts of nickel-based self-fluxing alloy powder, 20 parts of WC, 7 parts of Ti3Al alloy, 12 parts of α-ZrP, 8 parts of molybdate, 2 parts of silicate, 7 parts of SiO2 and 6 parts of Al2O3, 1 part of cerium oxide, and 1 part of lanthanum oxide;

[0092] The nickel-based self-fluxing alloy powder is NiCo23Cr17Al12Y0.5, and the average particle size of the nickel-based self-fluxing alloy powder is 25 μm; the molybdate is magnesium molybdate; the silicate is composed of mica powder (sand content: 0.5%, looseness: 2.7 g / cm 3 , pH value: 7, mesh size 325 mesh) and aluminum silicate.

[0093] The surface layer is attached to the surface of the middle layer, and the coating of the surface layer is a self-cleaning coating. In parts by weight, the self-cleaning coating comprises: 40 parts of TiO2, 20 parts of polytetrafluoroethylene dispersion emulsion (model DISP35), 30 parts of silica sol (Shandong Better New Materials, model S3010, sodium type silica sol with a content of 30% and a particle size of 10 to 15 nm), and 10 parts of α-methylphenethylmethyl hydrogen-containing polysiloxane (CAS No.: 63148-57-2).

[0094] Based on the above coating, this embodiment also provides a method for preparing the coating, which specifically includes the following steps:

[0095] S11. Use a sandblasting machine to spray steel shots of a certain size and speed onto the surface of the atomizing disk;

[0096] S21, spraying the bottom layer of spray coating onto the surface of the atomizing disk by using an atmospheric plasma spraying process to form a bottom layer on the surface of the atomizing disk;

[0097] Among them, the parameters of the atmospheric plasma spraying process include: argon flow rate of 35L / min, hydrogen flow rate of 10L / min, current control of 550A, power of 35kW, powder feeding argon flow rate of 3.0L / min, powder feeding speed of 70g / min, and spraying distance of 100mm.

[0098] S31, spraying the spray coating material of the intermediate layer onto the surface of the bottom layer by an atmospheric plasma spraying process, so as to form an intermediate layer on the surface of the bottom layer;

[0099] Among them, the parameters of the atmospheric plasma spraying process are: argon flow rate is 25L / min, hydrogen flow rate is 5L / min, current size is controlled to be 500A, power is 25kW, powder feeding argon flow rate is 1.0L / min, powder feeding speed is 50g / min, and spraying distance is 80mm.

[0100] S41, induction remelting the atomizing disk having the bottom layer and the middle layer, and then cooling to room temperature;

[0101] The parameters of the induction remelting include: a melting temperature of 1300° C. and a melting time of 120 s.

[0102] S51, applying a surface layer coating to the surface of the intermediate layer, and then drying to form a surface layer on the surface of the intermediate layer.

[0103] The thickness of the bottom layer is 100 μm, the thickness of the middle layer is 500 μm, and the thickness of the surface layer is 50 μm.

[0104] Example 2

[0105] This embodiment is further modified as follows based on the content disclosed in Embodiment 1:

[0106] The spray coating of the intermediate layer is: 20 parts of nickel-based self-fluxing alloy powder, 25 parts of WC, 10 parts of Ti3Al alloy, 15 parts of α-ZrP, 10 parts of molybdate, 5 parts of silicate, 7 parts of SiO2, 5 parts of Al2O3, 2 parts of cerium oxide, and 1 part of lanthanum oxide.

[0107] Example 3

[0108] This embodiment is further modified as follows based on the content disclosed in Embodiment 1:

[0109] The spray coating of the intermediate layer includes: 50 parts of nickel-based self-fluxing alloy powder, 20 parts of WC, 5 parts of Ti3Al alloy, 10 parts of α-ZrP, 2 parts of molybdate, 2 parts of silicate, 4 parts of SiO2 and 5 parts of Al2O3, 1 part of cerium oxide and 1 part of lanthanum oxide.

[0110] Example 4

[0111] This embodiment is further modified as follows based on the content disclosed in Embodiment 1:

[0112] The self-cleaning coating comprises: 20 parts of TiO2, 30 parts of polytetrafluoroethylene dispersion emulsion, 40 parts of silica sol, and 10 parts of α-methylphenethylmethyl hydrogen-containing polysiloxane.

[0113] Example 5

[0114] This embodiment is further modified as follows based on the content disclosed in Embodiment 1:

[0115] The self-cleaning coating comprises: 50 parts of TiO2, 10 parts of polytetrafluoroethylene dispersion emulsion, 20 parts of silica sol, and 20 parts of α-methylphenethylmethyl hydrogen-containing polysiloxane.

[0116] Example 6

[0117] This embodiment is further modified as follows based on the content disclosed in Embodiment 1:

[0118] The silicate is mica powder.

[0119] Example 7

[0120] This embodiment is further modified as follows based on the content disclosed in Embodiment 1:

[0121] The silicate is aluminum silicate.

[0122] Example 8

[0123] This embodiment is further modified as follows based on the content disclosed in Embodiment 1:

[0124] The parameters of the induction remelting include: a melting temperature of 1400° C. and a melting time of 60 s.

[0125] Comparative Example 1

[0126] This comparative example is further modified as follows based on the contents disclosed in Example 1:

[0127] No primer is provided in the coating.

[0128] Comparative Example 2

[0129] This comparative example is further modified as follows based on the contents disclosed in Example 1:

[0130] No surface layer is provided in the coating.

[0131] Comparative Example 3

[0132] This comparative example is further modified as follows based on the contents disclosed in Example 1:

[0133] No Ti3Al alloy is added to the spray coating of the intermediate layer.

[0134] Comparative Example 4

[0135] This comparative example is further modified as follows based on the contents disclosed in Example 1:

[0136] No α-ZrP is added to the spray coating of the intermediate layer.

[0137] Comparative Example 5

[0138] This comparative example is further modified as follows based on the contents disclosed in Example 1:

[0139] No molybdate is added to the spray coating of the intermediate layer.

[0140] Comparative Example 6

[0141] This comparative example is further modified as follows based on the contents disclosed in Example 1:

[0142] No silicate is added to the spray coating of the intermediate layer.

[0143] Comparative Example 7

[0144] This comparative example is further modified as follows based on the contents disclosed in Example 1:

[0145] No TiO2 is added to self-cleaning coatings.

[0146] Comparative Example 8

[0147] This comparative example is further modified as follows based on the contents disclosed in Example 1:

[0148] No polytetrafluoroethylene dispersion is added to the self-cleaning coating.

[0149] Comparative Example 9

[0150] This comparative example is further modified as follows based on the contents disclosed in Example 1:

[0151] No silica sol is added to the self-cleaning coating.

[0152] Comparative Example 10

[0153] This comparative example is further modified as follows based on the contents disclosed in Example 1:

[0154] α-Methylphenethylmethyl hydrogen-containing polysiloxane is not added to the self-cleaning coating.

[0155] The surface coatings of the atomizer disks obtained in Examples 1 to 8 and Comparative Examples 1 to 10 were subjected to performance tests, and the results are shown in Tables 1 and 2. High temperature resistance test method: The atomizer disk was placed in a high temperature furnace, heated to 1300°C and kept warm for 1 hour, cooled with the furnace, and the coating surface was observed to see if cracking or melting occurred. Adhesion was measured according to GB / T9286-1998. The time it took for the surface coating of the atomizer disk to corrode to the atomizer disk substrate in 5% sulfuric acid and 5% sodium hydroxide solution was recorded.

[0156] Table 1 Performance of the atomizing disk surface coating of Examples 1 to 8

[0157]

[0158] As shown in Table 1, the microhardness of the coatings of Examples 1 to 8 is HV≥500, the porosity is <0.5%, the service life of the atomizer disk with the coating on the surface is >12 months, the time for corrosion to the protective sleeve substrate in 5% sulfuric acid solution is >9000h, and the time for corrosion to the protective sleeve substrate in 5% sodium hydroxide solution is >9100h. The formaldehyde degradation rate is >60%, the water contact angle of the coating surface is greater than 100°, and the oil (n-hexadecane) contact angle is >60°. Examples 6 and 7 are single silicates, and the service life performance is reduced.

[0159] Table 2 Performance of the atomizing disk surface coating of Comparative Examples 1 to 10

[0160]

[0161] It can be seen from Table 1 that in Comparative Example 1, no bottom layer is set, resulting in low adhesion of the coating; in Comparative Example 2, no surface layer is set, resulting in a serious decrease in the self-cleaning performance; in Comparative Examples 3 to 6, the spray coating of the middle layer lacks important components, resulting in a slight decrease in corrosion resistance; in Comparative Examples 7 to 10, the self-cleaning coating lacks important components, resulting in a slight decrease in self-cleaning performance.

[0162] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.

[0163] In the description of the specification of the present application, the terms "include", "comprise", etc. mean "including but not limited to". In this article, "and / or" describes the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. Wherein A and B can be singular or plural. In this article, "at least one" means one or more, and "plurality" means two or more. "At least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all represent: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple, respectively.

[0164] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.

Claims

1. A scour-resistant coating for an atomizing disk, characterized in that: The coating comprises: A bottom layer, the bottom layer is attached to the surface of the atomizing disk, and the spray coating of the bottom layer is a high-molybdenum-nickel-based self-fluxing alloy powder; an intermediate layer, the intermediate layer being attached to the surface of the bottom layer, wherein the spray coating material of the intermediate layer comprises, by weight: 20 to 50 parts of nickel-based self-fluxing alloy powder, 10 to 25 parts of WC, 5 to 10 parts of Ti3Al alloy, 5 to 15 parts of α-ZrP, 2 to 10 parts of molybdate, 2 to 5 parts of silicate, 5 to 10 parts of SiO2 and 4 to 8 parts of Al2O3, 1 to 3 parts of cerium oxide, and 1 to 3 parts of lanthanum oxide; and The surface layer is attached to the surface of the middle layer. The coating of the surface layer is a self-cleaning coating. The components of the self-cleaning coating include: TiO2, polytetrafluoroethylene dispersion emulsion, silica sol, α-methylphenethylmethyl hydrogen-containing polysiloxane.

2. The coating according to claim 1, characterized in that The nickel-based self-fluxing alloy powder includes one or more of NiCo23Cr17Al12Y0.5, NiCo23Cr20Al8.5Ta4Y0.1 and CoNi32Cr21Al8Y0.5, and the average particle size of the nickel-based self-fluxing alloy powder is 20-30 μm.

3. The coating according to claim 1, characterized in that The silicate includes one or more of mica powder, calcium silicate, aluminum silicate and alkali metal silicate, and the molybdate includes one or more of alkali metal molybdate, magnesium molybdate and thallium molybdate.

4. The coating according to claim 3, characterized in that The silicate is mica powder and aluminum silicate, and the mass ratio of the mica powder to the aluminum silicate is (1-3):

1.

5. The coating according to claim 1, characterized in that The self-cleaning coating comprises, by weight, 20 to 50 parts of TiO2, 10 to 30 parts of polytetrafluoroethylene dispersion emulsion, 20 to 40 parts of silica sol, and 10 to 20 parts of α-methylphenethylmethyl hydrogen-containing polysiloxane.

6. The coating according to claim 1, characterized in that The thickness of the bottom layer is 50-100 μm, the thickness of the middle layer is 200-500 μm, and the thickness of the surface layer is 40-80 μm.

7. The coating according to claim 1, characterized in that The coating meets the following properties: microhardness HV≥500, porosity<0.5%, and the service life of the atomizing disk with the coating on the surface is>12 months.

8. A method for preparing a coating according to any one of claims 1 to 7, characterized in that: The method comprises: The atomizing disk is shot peened; Spraying a bottom layer of spray paint onto the surface of the atomizing disk to form a bottom layer on the surface of the atomizing disk; Spraying the spray coating material of the intermediate layer onto the surface of the bottom layer to form an intermediate layer on the surface of the bottom layer; The atomizing disk having the bottom layer and the middle layer is subjected to induction remelting, and then cooled to room temperature; The coating material of the surface layer is applied to the surface of the intermediate layer and then dried to form the surface layer on the surface of the intermediate layer.

9. The method according to claim 8, characterized in that The spraying adopts an atmospheric plasma spraying process, and the parameters of the atmospheric plasma spraying process include: an argon flow rate of 25 to 35 L / min, a hydrogen flow rate of 5 to 10 L / min, a current control of 500 to 550 A, a power of 25 to 35 kW, a powder feeding argon flow rate of 1.0 to 3.0 L / min, a powder feeding speed of 50 to 70 g / min, and a spraying distance of 80 to 100 mm.

10. The method according to claim 8, characterized in that The parameters of the induction remelting include: a melting temperature of 1300 to 1400° C. and a melting time of 60 to 180 seconds.

Citation Information

Patent Citations

  • A high-temperature resistant and erosion-resistant composite coating for a thin-walled titanium alloy substrate and its preparation method

    CN114016028B

Cited By

  • Preparation method of in-situ modified and reinforced atomic gas chamber glass bulb

    CN121004545A